Hospitalization for Community Acquired Pneumonia in Alberta First Nations Aboriginals Compared with Non-First Nations Albertans - Thomas J Marrie; Keumhee C Carriere; Yan Jin; David H Johnson (Canadian Respiratory Journal)
BACKGROUND: The rates and outcomes of hospital admission for community-acquired pneumonia between First Nations Aboriginal and non-First Nations groups were compared.